Basic Concepts of Stock Option Pricing Models Traded in the Capital Market - Ibrahim, Riza Andrian; Azahra, Astrid Sulistya; Kalfin; Saputra, Moch Panji Agung (Communication In Research And Publications, 2024)
An option, in the world of capital markets, is a right based on an agreement to buy or sell a commodity, financial securities, or a foreign currency at an agreed price at any time within a three-month contract period. Factors that determine the value of an option include the current price of the stock, intrinsic value, expiration time or time value, volatility, interest rate, and cash dividends paid. Some options pricing models use this parameter to determine the fair market value of an option. This paper aims to learn the basic concepts of option pricing. The method used in studying the pricing of options is a literature review, which is an activity to collect scientific data, especially in the form of theories, methods, or research that has been carried out previously, either in the form of books, manuscripts, journals, and others that already exist in the library. Based on the results of the study, concepts, scientific findings, and method innovations that have been achieved previously are obtained, which are very relevant and useful for understanding the determination of stock option prices. An option, in the world of capital markets, is a right based on an agreement to buy or sell a commodity, financial securities, or a foreign currency at an agreed price at any time within a three-month contract period. Factors that determine the value of an option include the current price of the stock, intrinsic value, expiration time or time value, volatility, interest rate, and cash dividends paid. Some options pricing models use this parameter to determine the fair market value of an option. This paper aims to learn the basic concepts of option pricing. The method used in studying the pricing of options is a literature review, which is an activity to collect scientific data, especially in the form of theories, methods, or research that has been carried out previously, either in the form of books, manuscripts, journals, and others that already exist in the library. Based on the results of the study, concepts, scientific findings, and method innovations that have been achieved previously are obtained, which are very relevant and useful for understanding the determination of stock option prices.